Crime of ecocide in Ukraine – environmental consequences of Russian military aggression - Ihor Kozak (Studia Prawnicze KUL, 2024)
Even though the definition of the crime of ecocide was proposed by the Independent Expert Panel in 2021 it has not been incorporated into any international agreement yet. The Russian military aggression in Ukraine has demonstrated that the concept of ecocide is still relevant. The aim of the article is to analyse the concept of ecocide and to show that certain actions of the Russian army directed against the natural environment in Ukraine meet the criteria of the crime of ecocide, and therefore that these actions were unlawful, intentional, and committed with the awareness that they may result in serious and long-term or widespread damage to the environment.